Rapid Cytoplasmic Turnover of Yeast Ribosomes in Response to Rapamycin Inhibition of TOR - Pestov, Dimitri G. (American Society for Microbiology, 2012)
The target of rapamycin (TOR) pathway is the central regulator of cell growth in eukaryotes. Inhibition of TOR by rapamycin elicits changes in translation attributed mainly to altered translation initiation and repression of the synthesis of new ribosomes. Using quantitative analysis of rRNA, we found that the number of existing ribosomes present in a Saccharomyces cerevisiae culture during growth in rich medium rapidly decreases by 40 to 60% when the cells are treated with rapamycin. This process is not appreciably affected by a suppression of autophagy, previously implicated in degradation of ribosomes in eukaryotes upon starvation. Yeast cells deficient in the exosome function or lacking its cytoplasmic Ski cofactors show an abnormal pattern of rRNA degradation, particularly in the large ribosomal subunit, and accumulate rRNA fragments after rapamycin treatment and during diauxic shift. The exosome and Ski proteins are thus important for processing of rRNA decay intermediates, although they are probably not responsible for initiating rRNA decay. The role of cytoplasmic nucleases in rapamycin-induced rRNA degradation suggests mechanistic parallels of this process to nutrient-controlled ribosome turnover in prokaryotes. We propose that ribosome content is regulated dynamically in eukaryotes by TOR through both ribosome synthesis and the cytoplasmic turnover of mature ribosomes.